PENGARUH FRAKSI VOLUME TERHADAP KEKUATAN TARIK DAN BENDING KOMPOSIT SERAT SERABUT KELAPA BERMATRIKS POLIESTER - Muhammad Aizul Haq; Viktor Naubnome; Najmudin Fauji (ROTOR, 2022)
With natural fibers, namely coconut fibers that are easily found in the surrounding environment and literature studies that have been carried out, starting from the alkalization process, volume fraction, fiber length and utilization which will be used for fiberboard, the author wants to make a composite of coconut fiber fibers and do some The tests are tensile test and bending test. The tensile test results show the smallest tensile strength value at 10% fiber volume variation of 14.64 MPa and the largest tensile strength at 30% volume fraction variation with a value of 20.90 MPa. Increase in fiber volume variation 10% to variation The bending test results show the smallest bending strength value at 10% fiber volume variation of 34.81.64 MPa and the largest tensile strength at 30% volume fraction variation with a value of 49.41 MPa. The increase in the volume of the coco fiber fraction which is directly proportional to the tensile and bending strength values ​​is due to the increasing contribution of the fiber to withstand the load.